UTILIZING POTENTIAL OF COASTAL RESOURCES FOR THE WELFARE OF FISHERMEN IN THE WEST COAST REGION OF BULELENG REGENCY - I Nyoman Sukraaliawan; A.A. Ngurah Anom Kumbara; A.A. Bagus Wirawan; I Gde Made Metera (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2021)
This research was conducted in the West coast of Buleleng Regency with the aim of describing the potential of coastal resources for the welfare of fishing communities. The method used in this research is a survey supported by the observation method. Sampling with purposive sampling technique. Data analysis was carried out using qualitative descriptive analysis techniques and SWOT analysis. The results showed that the West coast resources in Buleleng Regency were in the form of biological resources, namely fishery potential and coral reefs. The potential of these coastal resources can be utilized to improve the welfare of the community through fish farming, coral reef conservation, training to improve tourism services, and providing fish auction sites. The role of other stakeholders such as academics, businessmen, Keywords: coastal resource potential, fishermen's welfare, coastal areas